Finding the Space Between: Leading for Cultural Safety in Australian Public Libraries. Issue 3 (2nd July 2020) - Masterson, Maeva
ABSTRACT: This paper reviews the research literature in Library and Information Sciences in Australia as well as related disciplines in Australia and internationally with the purpose of identifying leadership approaches best suited for developing and supporting culturally safe libraries in Australia. The paper identifies a lack of debate within Australian Library and Information Sciences in respect to cultural safety and leadership. It looks to research conducted into leadership approaches in related disciplines in Australia and internationally and explores several leadership approaches. It concludes that the intercultural leadership approach, an approach developed with Aboriginal Australians in the Northern Territory provides Australian library leaders with the most authoritative approach to leadership when embarking on developing culturally safe libraries. Implications for practice also suggest that increasing discussion and research into leadership approaches for Australian libraries is fundamental to growing the capacity of the Australian library sector to conceptualise and discuss leadership strategically and with purpose.